2018
DOI: 10.1097/prs.0000000000004841
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Validated Quality-of-Life Patient-Reported Outcome Measures in Pediatric Plastic Surgery

Abstract: This review found that generic patient-reported outcome measures were used most often, construct validity was used most frequently, physical functioning domains had the highest reliability, and the number of items or cost of a patient-reported outcome measure was not related to its frequency of use. Considered together, this information may inform the future development or selection of patient-reported outcome measures in pediatric plastic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The patient-reported outcomes measure (PROM) evaluates a patient's quality of life by the way of scales to promote communication, inspect and identify HRQOL issues, enhance patient-centered treatment, and increase patient satisfaction [14]. PROM is widely used in HRQOL and combines all aspects of emotional, psychological, physical, and social functions, and even includes an individual's subjective perception of health [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The patient-reported outcomes measure (PROM) evaluates a patient's quality of life by the way of scales to promote communication, inspect and identify HRQOL issues, enhance patient-centered treatment, and increase patient satisfaction [14]. PROM is widely used in HRQOL and combines all aspects of emotional, psychological, physical, and social functions, and even includes an individual's subjective perception of health [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] The patient-reported outcomes measure (PROM) evaluates a patient's quality of life by the way of scales to promote communication, inspect and identify HRQOL issues, enhance patient-centered treatment, and increase patient satisfaction. [14] PROM is widely used in HRQOL and combines all aspects of emotional, psychological, physical, and social functions, and even includes an individual's subjective perception of health. [15,16] Over the years, there has been considerable progress in the measurement, analysis, and interpretation of PROM, which has been validated by multifarious studies.…”
Section: Introductionmentioning
confidence: 99%
“…Patient-reported acceptability and intelligibility of speech as well as participation in communication were also included in the initial COS. QOL refers to the judgment of value placed on patient's health-related experiences. Roller et al demonstrated that the majority of PRO instruments used in pediatric plastic surgery are generic, rather than specific to the condition being treated (Roller et al, 2018). Interestingly, such measures tend not to be responsive to changes in functional status as a result of surgical intervention (Schönmeyr et al, 2015).…”
Section: Patient-reported Outcomesmentioning
confidence: 99%